Implementasi Pembelajaran Matematika Realistik untuk Meningkatkan Hasil Belajar Siswa Kelas II SD Negeri 30 Manganti - Nur Azizah; Refnywidialistuti; Lia Rismawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This research aims to describe or illustrate the implementation of realistic mathematics learning as a solution to improve the learning outcomes of class II students at SD Negeri 30 Manganti. The PMR approach that links mathematical concepts with real contexts is expected to increase student confidence, motivation in learning, activeness and understanding through the use of concrete media. The methods used in this study include discussions to develop students' critical thinking skills and student completeness which is calculated using the Minimum Completeness Criteria (KKM) guidelines by calculating the number of students who have completed and the percentage of classical completeness. This study shows an increase in the mathematics learning outcomes of class II students at SD Negeri 30 Manganti on measurement material after the implementation of realistic mathematics learning. at the end of cycle I, the average student score reached 81.75 with 5 students completing and 3 students not completing while at the end of cycle II the average score increased to 91.87 with 7 students completing and only 1 student not completing. These results identify that realistic mathematics learning is effective in improving student understanding so that the target of learning completeness can be achieved in cycle II.